High cardiometabolic risk in healthy Chilean adolescents: associations with anthropometric, biological and lifestyle factors. Issue 3 (20th May 2015) - Burrows, Raquel; Correa-Burrows, Paulina; Reyes, Marcela; Blanco, Estela; Albala, Cecilia; Gahagan, Sheila
Abstract: Objective: To analyse the prevalence of cardiovascular risk factors in healthy adolescents of low to middle socio-economic status and to study the influence of anthropometric, biological and lifestyle factors on the risk of metabolic syndrome (MetS). Design: Cross-sectional study. BMI, waist circumference, blood pressure, fat and lean mass (by dual-energy X-ray absorptiometry), TAG, HDL-cholesterol, glucose, insulin, homeostatic model assessment–insulin resistance index (HOMA-IR), food intake and physical activity were measured. Cardiovascular risk factors were defined using the International Diabetes Federation criteria and insulin resistance using HOMA-IR ≥2·6. Bivariate and multivariate regressions examined the associations between MetS and anthropometric, biological and lifestyle factors. Setting: Observational cohort study including Chilean adolescents, who were part of a follow-up study beginning in infancy. Subjects: Adolescents aged 16–17 years ( n 667). Results: In the sample, 16·2 % had obesity and 9·5 % had MetS. Low HDL-cholesterol (69·9 %), abdominal obesity (33·3 %) and fasting hyperglycaemia (8·7 %) were the most prevalent cardiovascular risk factors. In males, obesity (OR=3·7; 95 % CI 1·2, 10·8), insulin resistance (OR=3·0; 95 % CI 1·1, 8·2), physical inactivity (OR=2·9; 95 % CI 1·1, 7·7) and sarcopenia (OR=21·2; 95 % CI 4·2, 107·5) significantly increased the risk of MetS. In females, insulin resistance (OR=4·9; 95 % CI 1·9, 12·6) and sarcopenia (OR=3·6; 95 % CI 1·1, 11·9) were significantly associated with MetS. Conclusions: High prevalences of obesity, abdominal obesity, dyslipidaemia, fasting hyperglycaemia and MetS were found in healthy adolescents. In both sexes, sarcopenia and insulin resistance were important risk factors of MetS. Promotion of active lifestyles at the school level and regulation of the sale of energy-dense foods are needed.